Elder Companion Overview - Elizabeth B. Bolton (EDIS, 2004)
The Elder Companion training program is designed to train persons interested in becoming employed by local service providers as sitter/companions for the elderly. The objective of the program is to help participants develop the necessary skills to provide high-quality care including: assistance with daily living activities, home management services and companionship for the elderly adult. This document is FCS5246/FY586, one of a series of the Department of Family, Youth and Community Sciences, University of Florida, UF/IFAS, Gainesville 32611. First published: September 1999. Revised: January 2004.